Ekoglasnost and Eco-transformation. Bulgarian Environmental Movement in the First Years of the Political Transformation - Czekalski, Tadeusz (Balcanica Posnaniensia. Acta et studia, 2020)
The article discusses the origin and development of the ecological movement in Bulgaria in the first period of political transformation, against the background of similar experiences of Balkan countries. In the Balkan reality, the social activity of ecological groups is perceived as an example of the penetration of Western European cultural patterns, but also as an effect of "ecological pressure" resulting from the aspirations of South-Eastern European countries to integrate with European structures. To a small extent, the contemporary ecological sensitivity of the inhabitants of the Balkans refers to earlier experiences, such as those from the first decade of the political transformation. Against this background, the birth of the "indigenous" ecological movement in Bulgaria and its significant participation in the downfall of Todor Zhivkov's regime can be considered an exceptional phenomenon.